PENGARUH KUALITAS JASA TERHADAP LOYALITAS NASABAH KREDIT (Studi kasus pada PT.BPR - BKK GROGOl) - Marniyati, Sabar; Trisnowati, Juni (Surakarta Management Journal, 2020)
This research aim to know the effect of service quality to customer loyalty with customer satisfaction in mediator variable in customer Banking in BPR – BKK Grogol.  The analysis in this research used multiple linear regression test,  t test, F test and determination coefficient test. The result of this research shown reliability,  responsiveness, assurance, empathy, and tangibles are positively effects to customer loyalty in model I and not significance in model II. Significance test value of  F = 0,000. That’s mean there are the effect simulating of reliability,  responsiveness, assurance, empathy, and tangibles to customer loyalty. The t t result only variable assurance and tangible to partial effect on customer loyalty. R2 test (determination coefficient) is 0,512. It means independent variables ability (reliability, responsiveness, assurance, empathy, and tangibles) in explaining dependent variable (customer loyalty) is 51,2%.